The peculiarities in reformation of the future technology teachers preparation in the Nordic Countries in the end of XX century - ZHERNOKLIEIEV, Igor (Journal of Education, Technology and Computer Science, 2016)
The article examines the peculiarities in reformation of the future technology teachers preparation in the Nordic countries in the end of XX century which defined their success and international recognition in the international educational space. Based on Nordic authentic scientific literature, it was revealed the particularities of educational reforms in each of the Nordic countries.